The Place of Physical Infrastructure in Realizing Nigeria’s Vision 20: 2020 - Paul B, Akhalumeh; Izien, Ohiokha Friday (International Journal of Management and Sustainability, 2013)
This paper examines how infrastructure will play a vital role in the realization of Nigeria’s Vision 20: 2020. The objective is to assess the adequacy of Nigerian infrastructural base as a pre-requisite to the realization of the laudable Vision 20:2020. It is expected that Nigerian government will use the result of this study to evaluate Nigeria’s infrastructure so that appropriate steps can be taken to address the palpable deficit in infrastructure. The study used data from secondary source of published materials from credible internet web sites to analyze the current Nigerian situation. The results of the study reveal that though the project of Vision 20:2020 is grandiose, there seems to be a lack of corresponding will to achieve the ideals of the Vision as evident in the deficit in our transport infrastructure, electricity power generation and technological impetus as shown by the standards of Nigerian tertiary education (universities and others). The study therefore recommends amongst others that: there should be sufficient fiscal discipline, transparency, good governance and accountability to ensure that there is adequate commitment to the Vision: the transport infrastructure should be expanded and upgraded, with provision made for their maintenance; Nigeria should take concerted steps to address the problem of power generation and distribution, and Nigerian tertiary education should be restructured.